(untitled) (Asian Journal of Plant Biology, 2014)
The Arabidopsis AXR4 gene product is involved in polar targeting of AUX1 an auxin influx carrier, to the plasma membrane (Dharmasiri et al. 2006). The AXR4 gene encodes a protein of 473 amino acids and is predicted as a Type II, integral membrane protein with a short N terminal sequence, a single transmembrane region and a large C terminal domain. The C terminus domain of AtAXR4 referred to as AtAXR4 C, was expressed as a recombinant protein in Escherichia coli and used as an antigen to generate polyclonal antibody. The antibody recognized a protein of approximately 54 kDa in the membrane fractions prepared from Arabidopsis thaliana. The availability of anti-AXR4 antibody will contribute towards elucidation of AXR4 biochemical properties and its molecular function.